IGF1 stimulates crypt expansion via differential activation of 2 intestinal stem cell populations. Issue 7 (2nd April 2015) - Van Landeghem, Laurianne; Santoro, M. Agostina; Mah, Amanda T.; Krebs, Adrienne E.; Dehmer, Jeffrey J.; McNaughton, Kirk K.; Helmrath, Michael A.; Magness, Scott T.; Lund, P. Kay
ABSTRACT: Insulin‐like growth factor 1 (IGF1) has potent trophic effects on normal or injured intestinal epithelium, but specific effects on intestinal stem cells (ISCs) are undefined. We used Sox9‐enhanced green fluorescent protein (EGFP) reporter mice that permit analyses of both actively cycling ISCs (Sox9‐EGFP Low ) and reserve/facultative ISCs (Sox9‐EGFP High ) to study IGF1 action on ISCs in normal intestine or during crypt regeneration after high‐dose radiation‐induced injury. We hypothesized that IGF1 differentially regulates proliferation and gene expression in actively cycling and reserve/facultative ISCs. IGF1 was delivered for 5 days using subcutaneously implanted mini‐pumps in uninjured mice or after 14 Gy abdominal radiation. ISC numbers, proliferation, and transcriptome were assessed. IGF1 increased epithelial growth in nonirradiated mice and enhanced crypt regeneration after radiation. In uninjured and regenerating intestines, IGF1 increased total numbers of Sox9‐EGFP Low ISCs and percentage of these cells in M‐phase. IGF1 increased percentages of Sox9‐EGFP High ISCs inS‐phase but did not expand this population. Microarray revealed that IGF1 activated distinct gene expression signatures in the 2 Sox9‐EGFP ISC populations. In vitro IGF1 enhanced enteroid formation by Sox9‐EGFP High facultative ISCs but not Sox9‐EGFP Low actively cycling ISCs. Our data provide new evidence that IGF1 activates 2 ISC populations via distinct regulatory pathways to promote growth of normal intestinal epithelium and crypt regeneration after irradiation.—Van Landeghem, L., Santoro, M. A., Mah, A. T., Krebs, A. E., Dehmer, J. J., McNaughton, K. K., Helmrath, M.A., Magness, S.T., Lund, P. K. IGF1 stimulates crypt expansion via differential activation of 2 intestinal stem cell populations. FASEB J . 29, 2828‐2842 (2015). www.fasebj.org